THE ANALYSIS OF THE STRATEGY OF TEMPORAL STREET REPAIRS TO VEHICLE OPERATION COSTS (CASE STUDY: CANDIPURO HIGHWAY, LUMAJANG) - Rizqi Eka Faiqatul Maghfiroh; Akhmad Hasanuddin; Sri Sukmawati (Jurnal Rekayasa Sipil dan Lingkungan, 2019)
Candipuro highway, Candipuro District, Lumajang Regency is a road section which is passed by sand loaded trucks so that this road receives excessive loads. It can be seen from the presence of perforation damages, hair cracks, longitudinal and transverse cracks, edge cracks and polished aggregate. The damages on the road can disrupt the comfort and safety of drivers and affect to Vehicle Operating Cost (VOC). There is 2 maintenance method used in this research. The first method was an analysis of routine roadwork strategies once a year and second method every 3 years for 9 years to find out the most efficient cost for roadwork and operating cost for vehicles. ND Lea Consultant which focused on the aspect of pavement was used as the method for Vehicle Operating Cost. An economic feasibility analysis was used to determine the appropriate strategy using which strategy has a cheaper fee. The results of the calculation of routine roadwork every 1 year during 9 years were Rp3.459.436.869,42 and periodic roadwork 3 years for 9 years was Rp5.021.403.850,96. The total operating cost of car vehicles due to routine maintenance once a year during 9 years was Rp4.391.248.161,16 and periodic maintenance for 3 years during the 9 years was Rp4.391.248.161,16. Therefore, the efficient handling strategy was routine maintenance once a year. It was because this alternative has cheaper than periodic maintenance. Ruas Jalan Raya Candipuro, Kecamatan Candipuro Kabupaten Lumajang merupakan ruas jalan yang dilewati truck pengangkut pasir sehingga ruas jalan ini menerima beban berlebih. Hal ini dapat dilihat dari adanya kerusakan berlubang, retak rambut, retak memanjang dan melintang, retak tepi dan pelepasan butiran. Kerusakan jalan dapat mengganggu kenyamanan maupun keselamatan pengendara dan dapat mempengaruhi Biaya Operasi Kendaraan (BOK). Terdapat 2 metode perbaikan jalan pada penelitian ini, metode pertama adalah secara rutin setiap 1 tahun sekali dan metode kedua secara berkala setiap 3 tahun sekali selama 9 tahun untuk mengetahui biaya yang paling efisien untuk perbaikan jalan serta biaya operasi terhadap kendaraan. Metode untuk Biaya Operasi Kendaraan menggunakan ND Lea Consultant yang menitikberatkan pada aspek perkerasan jalan. Analisa kelayakan ekonomi digunakan untuk penentuan stategi yang sesuai dengan memilih biaya yang paling kecil, sehingga efisien dari segi biaya. Hasil dari perhitungan untuk perbaikan jalan secara rutin setiap 1 tahun sekali selama 9 tahun adalah Rp3.459.436.869,42 dan perbaikan jalan secara berkala 3 tahun sekali selama 9 tahun adalah Rp5.021.403.850,96. Total Biaya Operasi Kendaraan mobil akibat pemeliharaan rutin 1 tahun sekali selama 9 tahun adalah Rp4.391.248.161,16 dan pemeliharaan berkala 3 tahun sekali selama 9 tahun adalah Rp4.941.996.380,06. Strategi penanganan yang efektif adalah pemeliharaan rutin 1 tahun sekali, karena alternatif ini memiliki biaya yang lebih kecil daripada pemeliharaan berkala.